2017
DOI: 10.1002/ecy.1642
|View full text |Cite
|
Sign up to set email alerts
|

Biotic interactions mediate the influence of bird colonies on vegetation and soil chemistry at aggregation sites

Abstract: Colonial-nesting organisms can strongly alter the chemical and biotic conditions around their aggregation sites, with cascading impacts on other components of the ecosystem. In tropical Australia, Metallic Starlings (Aplonis metallica) nest in large colonies far above the forest canopy, in emergent trees. The ground beneath those trees is open, in stark contrast to the dense foliage all around. We surveyed the areas beneath 27 colony trees (and nearby randomly chosen trees lacking bird colonies) to quantify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 40 publications
0
32
0
2
Order By: Relevance
“…Small numbers of starlings drop enough guano and organic matter to attract invertebrates on which the toads feed. Even at abandoned sites, the abundance of invertebrates in the rich soils created by the starlings (Natusch et al 2017) allows toads to continue to gain a nutritional advantage from the colonies long after they are abandoned.…”
Section: Discussionmentioning
confidence: 99%
“…Small numbers of starlings drop enough guano and organic matter to attract invertebrates on which the toads feed. Even at abandoned sites, the abundance of invertebrates in the rich soils created by the starlings (Natusch et al 2017) allows toads to continue to gain a nutritional advantage from the colonies long after they are abandoned.…”
Section: Discussionmentioning
confidence: 99%
“…; Natusch et al . in press). Although the foraging activity of turkeys and other birds exposes some seeds and invertebrates within the soil, soil turnover by pigs massively increases avian accessibility to otherwise‐unreachable resources.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research at our study site has shown that pigs kill seedlings beneath colony trees via direct consumption (or indirectly through their foraging activities), creating a zone of little or no vegetation surrounding the tree (Natusch et al . in press). This begs the question: what did the environment beneath starling colonies look like before pigs were introduced?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The birds attract an array of local predators that feed on fallen nestlings, and invertebrates in the guano-enriched soil beneath the tree ( Natusch et al 2016 ; see Figure 1 ). Because feral pigs Sus scrofa kill any seedlings that grow in this nutrient-rich soil, each bird-colony tree usually has an area of open ground beneath it measuring ∼140 m 2 ( Natusch et al 2017b ). During the season when birds are breeding, the open ground beneath each bird-nesting tree often contains predatory mammals (dingos Canis lupis dingo ), birds (scrub-fowl Megapodius reinwardt , cockatoos Cacatua galerita and Probosciger aterrimus ), snakes ( Boiga irregularis , Liasis fuscus , Morelia amethistina , and Stegonotus cucullatus ), and amphibians ( Rhinella marina and Litoria infrafrenata ).…”
Section: Methodsmentioning
confidence: 99%